A public ethics defined by the majorities? some reflections from draft law on same - sex civil union - Sotelo Torres, Claudio Renato (2017)
This paper presents some considerations about the draft law on same–sex civil union, analyzed by the Congress of the Republic of Peru. Specifically, the impact of the beliefs of a significant number of Peruvian citizens in the delimitation of public and private ethics, due the influence of some pathologies in areas that can affect significantly fundamental rights. Instead, in this paper, are exposed some thoughts above the possibility that some religious beliefs can transcend the real of public ethics, when are used exclusively to promote fundamental rights and ensure human dignity.